A Review on the Use of Waste Plastic Oil as an Alternative Fuel for Diesel Engines - Kaewbuddee, Chalita; Maithomklang, Somkiat (Rajamangala University of Technology Tawan-ok Research Journal, 2025)
Plastic waste is one of the most pressing global environmental challenges, escalating in severity and urgently requiring sustainable management solutions. Converting plastic waste into energy—particularly in the form of waste plastic oil (WPO) via pyrolysis—has garnered widespread attention in the research community. Such interest is due to its potential to reduce persistent, non-biodegradable waste while simultaneously generating a viable alternative energy source. This review article gathers, examines, and combines current research about WPO, looking at its physical and chemical traits, how it performs in engines, how it burns, and its exhaust emissions compared to regular diesel fuel. The findings reveal that WPO possesses a hydrocarbon composition and heating value similar to fossil-based fuels and can be used in diesel engines with minimal modification. However, certain limitations remain, such as low cetane index, high viscosity, low flash point, and elevated levels of specific emissions, including NOX and CO, compared to diesel. In addition, this review identifies significant gaps in the current body of research, which has largely emphasized technical experimentation while overlooking economic evaluations and policy-related aspects. Issues such as the economic feasibility of WPO production systems, energy cost per unit, and the role of governmental support mechanisms are rarely addressed but are crucial for large-scale industrial implementation.